2015
DOI: 10.1186/s13613-015-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of antimicrobial resistance in Gram-negative bacilli

Abstract: The burden of multidrug resistance in Gram-negative bacilli (GNB) now represents a daily issue for the management of antimicrobial therapy in intensive care unit (ICU) patients. In Enterobacteriaceae, the dramatic increase in the rates of resistance to third-generation cephalosporins mainly results from the spread of plasmid-borne extended-spectrum beta-lactamase (ESBL), especially those belonging to the CTX-M family. The efficacy of beta-lactam/beta-lactamase inhibitor associations for severe infections due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
327
2
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(358 citation statements)
references
References 165 publications
(196 reference statements)
14
327
2
15
Order By: Relevance
“…Based on the analysis results, enterobacteria were predominant (62.16%) in Gram-negative bacilli, followed by 33.33% non-fermenting Gram-negative bacilli (NFGNB). Gramnegative bacilli (GNB) acquire genes that code for antibiotic resistance mechanisms and thus exacerbate the resulting infections (Ruppé et al, 2015). The rate of enterobacteria isolated in our study is higher than the 10.70% isolated by Jalalpoor (2011) and is lower than 74.51% reported by Debabza (2015).…”
Section: Distribution Of Distribution Of Nfgnbcontrasting
confidence: 68%
“…Based on the analysis results, enterobacteria were predominant (62.16%) in Gram-negative bacilli, followed by 33.33% non-fermenting Gram-negative bacilli (NFGNB). Gramnegative bacilli (GNB) acquire genes that code for antibiotic resistance mechanisms and thus exacerbate the resulting infections (Ruppé et al, 2015). The rate of enterobacteria isolated in our study is higher than the 10.70% isolated by Jalalpoor (2011) and is lower than 74.51% reported by Debabza (2015).…”
Section: Distribution Of Distribution Of Nfgnbcontrasting
confidence: 68%
“…A result which is in agreement with other study in Sothern Saudi Arabia which showeda percentage of77%, 16% and 7% for the isolated organisms in outpatient UTI ( El-Kersh et al, 2015). Previous studies (Gupta et al, 2011;AlJiffri et al, 2011;Pondei et al, 2012;Ahmad, 2012) (Ruppe et al, 2015). The existing data showed a wide variation in the prevalence of ESBL, AmpC and Carbapenemase from region to region or even from hospital to hospital in the same region ( Babypadmini and Appalaraju, 2004 Kumar et al, 2014 documented that antimicrobial sensitivity pattern of ESBL-producing E. coli showed that it was 100% susceptible to Imipenem however their results were not in agreement with our results in that the susceptibility to ESBL inhibitor combination drugs was almost the same as compared to non-ESBL producing E. coli.…”
Section: Resultsmentioning
confidence: 90%
“…If ESBL producers are to be expected, carbapenems should generally be preferred, even though several clinically relevant ESBL variants (temoneira β-lactamase, TEM; sulfhydryl variable type β-lactamase, SHV; cefotaxime-Munich β-lactamase, CTX-M) may retain susceptibility to piperacillin/tazobactam [154]. If the antibiogram reveals an ESBL pathogen to be susceptible to piperacillin/tazobactam, treatment of urinary tract infections is usually unproblematic; however, for bacteremia, no consensus has been reached regarding the adequacy of therapy due to the inoculum effect [155] and the serious implications of altered β-lactam pharmacokinetics in sepsis patients [156,157]. Whether antibiogram-directed treatment against ESBL-synthesizing pathogens should be conducted with piperacillin/tazobactam thus remains a decisionthatmustbe made on the basis of an individual risk-benefit assessment.…”
Section: Sepsis Of Unknown Source Without Pretreatmentmentioning
confidence: 99%